On the Sources of Some N.V. Gogol’s Records in the “Tarnovsky Notebook” - Irina A. Zaitseva (Studia Litterarum)
The presented work is directly related to the ongoing at the Institute of World Literature of the Russian Academy of Sciences preparation of the academic Complete Works of N.V. Gogol in 23 volumes. The article is devoted to the problem of establishing the sources of a number of texts introduced by Gogol’s hand in one of his notebooks, the so-called “Tarnovsky notebook” (1830–1834). The author of the article examines thematic intersections of part of these records with fragments of the Gogol letter dated April 2, 1830. The first of the records, indicating the author (K. Shtisser) and the title of his work, is first compared with the searched printed original. The article describes the volume and nature of its copying by Gogol, also it establishes the origin and authorship of the four “anonymous” texts written by Gogol’s hand in the “notebook.” The article includes the results of correlation of these texts with the primary sources, such as the volume and nature of the abbreviations when copying, lexical, stylistic, punctuation differences. The results of the research present options for the inclusion of attributed records in the upcoming Complete Works of N.V. Gogol, as well as the possibility of using the established facts when commenting on the mentioned letter.